Nonecotropic murine leukemia viruses in BALB/c and NFS/N mice: characterization of the BALB/c Bxv-1 provirus and the single NFS endogenous xenotrope. - Hoggan, M D (1986)
We used hybridization probes that react specifically with xenotropic and mink cell focus-forming virus envelope sequences to characterize the nonecotropic proviruses of BALB/c and NFS/N mice. Analysis of somatic cell hybrids with different BALB/c chromosomes showed that the 9 xenotropic and more than 20 MCF virus-related proviral sequences in this mouse were present on more than nine BALB/c chromosomes. Multiple copies were found on chromosomes 1, 4, 7, 12, and probably 11, and the copies found on a single chromosome were not identical by restriction enzyme mapping. We also identified and characterized the proviral sequences that give rise to infectious xenotropic virus in both BALB/c and NFS/N mice. BALB/c contains the major locus for induction of infectious virus in inbred mice, Bxv-1, which is on chromosome 1. We showed that this locus contains a single xenotropic provirus on an 18-kilobase HindIII fragment. Restriction enzyme analysis of a hybrid cell DNA that contains only the Bxv-1 xenotropic provirus showed that the Bxv-1 provirus contains restriction enzyme sites characteristic of the infectious virus induced from BALB/c fibroblasts. The Bxv-1 provirus and its flanking sequences also contain the same restriction sites as the provirus thought to contribute U3 long terminal repeat sequences to leukemogenic (class I) AKR MCF viruses. Analysis of cell hybrids made with the nonvirus-inducible strain NFS/N showed that the single xenotropic virus env gene of NFS mice, here termed Nfxv-1, is not on chromosome 1. Unlike that of Bxv-1, the restriction map of Nfxv-1 does not resemble that of any known infectious xenotropic virus including xenotropic viruses isolated from NFS mice. These data suggest that Bxv-1, but not Nfxv-1, is a full-length xenotropic provirus that can be transcribed directly to produce infectious virus.